Krajowy Mechanizm Prewencji Tortur w oczach funkcjonariuszy Służby Więziennej - Lasocik, Zbigniew; Męzik, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The purpose of this study is to present the results of research conducted among officers and employees of the Prison Service regarding the knowledge and opinions of representatives of this professional group on the National Mechanism for the Prevention of Torture (hereinafter also KMPT, Mechanism).
Keywords: tortury; kary; zasady humanitaryzmu; prawa człowieka